KUMARA - Kumara, M Fadjriansyah; Desfiarni, Desfiarni (SENDRATASIK UNP, 2019)
Abstract The creation of the dance Works "Kumara" aims to create creative dance works and train, educate the creative power of a choreographer or stylist to prepare the idea of being directed through an innovative motion as a language of communication in dance works.  The plot on the dance works "Kumara" tells of the child as the most injured victim when his parents decide to divorce. The form of presentation in the dance Works "Kumara" is symbolic of representational. The results of the study show that "Kumara" is a dance work inspired by the social phenomenon of life in which family integrity is the most important thing in a family. When the child becomes a victim of his parents ' farewell, the child's behavior in responding to divorce also varies depending on their age when the event occurs.  Children of divorce victims will tend to be more inclined, aggressive because of the erratic feeling. Silent culture will also arise due to parents ' divorce. The silent culture will be characterized by the absence of communication and dialogue between family members. The dance Works "Kumara" is a dramatic dance. The interpretation of the parents ' inner turmoil is manifested through motion, stage, make-up, fashion, lighting, and emphasized by the music. Keywords: Kumara, Dance Kumara, Perform Art